1919
DOI: 10.1086/622685
|View full text |Cite
|
Sign up to set email alerts
|

The Horizon of the Marine Jurassic of Utah

Abstract: FIG. I.-Contact of thin-bedded marine Jurassic limestone on white cross-bedded sandstone of La Plata group. One-half mile southwest of Teasdale, Utah. (Contact at black line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1951
1951
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Evidence of an erosional unconformity between the Moenkopi formation of Triassic age and the underlying Kaibab limestone of Permian age occurS in many places in northern Arizona and southern lTtah (McKee, 1938, p. 57-58;Gilluly, 1929, p. 81-82;Gilluly and Reeside, 1928, p. 64-65 ;Gregory and Moore, 1931, p. 45-46;Dake, 1920). Similar evidence is in the Capitol Reef area.…”
Section: Kaibab Limestonementioning
confidence: 87%
See 1 more Smart Citation
“…Evidence of an erosional unconformity between the Moenkopi formation of Triassic age and the underlying Kaibab limestone of Permian age occurS in many places in northern Arizona and southern lTtah (McKee, 1938, p. 57-58;Gilluly, 1929, p. 81-82;Gilluly and Reeside, 1928, p. 64-65 ;Gregory and Moore, 1931, p. 45-46;Dake, 1920). Similar evidence is in the Capitol Reef area.…”
Section: Kaibab Limestonementioning
confidence: 87%
“…Gregory and Moore (1931) examined the geology of the area in connection with their work in the Kaiparowits region to the south. Dake ( 1919Dake ( , 1920 outlined the stratigraphic sequence in the area and related it to the rest of the Colorado Plateau. The northeastern part of plate 1 covers the southern part of the San Rafael Swell area mapped by Gilluly (1929).…”
Section: Previous Workmentioning
confidence: 99%
“…The first descriptions of the Entrada Sandstone were made by scientists in the early 20 th century as part of geologic surveys of western Colorado and eastern Utah (Cross, 1907;Lupton, 1916;Emery, 1918;Dake, 1919;Longwell et al, 1923). Gilluly and Reeside (1928) were the first to differentiate the Entrada Sandstone as a distinct formation, naming it after the prominent Entrada Point located in the northern San Rafael Swell.…”
Section: Previous Workmentioning
confidence: 99%
“…yer part of an assemblage of beds which includes gypsum, sandstone, consolidated variegated muds, and lenses of conglomerate," and extends upward to "coal bearing fossiliferous Cretaceous." Other geologic studies (Gilluly and Reeside 1928, Dake 1919 showed that the "Jurassic" rocks noted by Howell, Gilbert, Dutton, and vValcott in the Parunuweap, Kanab, and Paria Valleys are widely exposed in east-central and southern Utah, where they comprise groups of strata strongly contrasted in composition and origin and are represented in the topography of distinctive forms. As these groups maintain their characteristic features over hundreds of square miles, names applied in local descriptions were gradually abandoned in favor of a comprehensive terminology; by agreement among field workers the Jurassic beds above the Navajo sandstone were subdivided into fiye formations-Carmel (at the base), Entrada, Curtis, Summerville, and Morrison.…”
Section: Jurassic Formations Previous Studiesmentioning
confidence: 99%